ANALISIS KELAYAKAN USAHA MINYAK SERAI WANGI (Cymbopogon nardus.L) DI KECAMATAN KUTAPANJANG KABUPATEN GAYO LUES - Endang Astuti; Siti Balqies Indra; Fiddini Alham; Thursina Mahyuddin (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
Citronella oil is one of the essential oil commodities that have the potential to be cultivated. Kutapanjang District is one of the sub-districts in Gayo Lues which is located in the 3rd largest producer of citronella. In producing citronella oil requires a large capital. The purpose of this study was to analyze the feasibility of citronella oil business in Kutapanjang District, Gayo Lues Regency. This study uses a farming analysis method, namely analyzing production costs, revenue, income, feasibility calculations using the R/C Ratio and B/C Ratio. Based on the results and discussion of the research that has been done, it can be concluded that the citronella oil business in Kutapanjang District is feasible to operate with revenues of Rp. 27,840,000.00, income of Rp. 17,195,528.00, R/C Ratio > 1 which is 2.61, B /C Ratio >1 which is 1.61.